Wedge-Shaped Pop-Up Structure in the Eslami Peninsula, Lake Urmia, Northwestern Iran - ALIZADEH, Akram; JANGJOO, Fayezeh (Acta geologica Sinica (Beijing), 2017)
Ancient subduction zones are characterized by metamorphic and orogenic belts. The Zagros Orogenic Belt comprises almost all sections of an ancient subduction zone along which Neo-Tethyan oceanic crust was subducted beneath central Iran. The Eslami Peninsula, as a part of the Zagros Orogenic Belt in Azerbaijan province, northwestern Iran, is situated between the Lake Urmia fore-arc basin and the Sahand Magmatic Arc. This region contains Eocene leucite dikes, trachyte, tephrite, phenolite, basanite and syenite. Volcanic features related to the Sahand are located in the eastern part of the Eslami Peninsula. In view of its relative age and composition, the Eslami Peninsula proposed as an outer arc of the Sahand Magmatic Arc that formed within the post-collisional setting of the central Iranian and Arabian plates. After subduction and contact of the two plates, a symmetric pop-up structure has been created by thrusting in the Zagros belt as a result of the collision processes. The injesction of dikes in the Eslami Peninsula is also a result of the continent continent collision.